Analysis of Large Geomagnetically Induced Currents During the 7–8 September 2017 Storm: Geoelectric Field Mapping - Anna Wawrzaszek; Agnieszka Gil; Renata Modzelewska; Bruce T. Tsurutani; Roman Wawrzaszek (Space Weather)
Abstract High temporal and high spatial resolution geoelectric field models of two Mäntsälä, Finnish pipeline geomagnetically induced current (GIC) intervals that occurred within the 7–8 September 2017 geomagnetic storm have been made. The geomagnetic measurements with 10 s sampling rate of 28 IMAGE ground magnetometers distributed over the north Europe (from 52.07° to 69.76° latitude) are the bases for the study. A GeoElectric Dynamic Mapping (GEDMap) code was developed for this task. GEDMap considers 4 different methods of interpolation and allows a grid of 0.05° (lat.) × 0.2° (lon.) spatial scale resolution. The geoelectric field dynamic mapping output gives both spatial and temporal variations of the magnitude and direction of fields. The GEDMap results show very rapid and strong variability of geoelectric field and the extremely localized peak enhancements. The magnitude of geoelectric fields over Mäntsälä at the time of the two GIC peaks were 279.7 and 336.9 mV/km. The comparison of the GIC measurements in Mäntsälä and our modeling results show very good agreement with a correlation coefficient higher than 0.8. It is found that the auroral electrojet geoelectric field has very rapid changes in both magnitude and orientation causing the GICs. It is also shown that the electrojet is not simply oriented in the east‐west direction. It is possible that even higher time resolution base magnetometer data of 1 s will yield even more structure, so this will be our next effort.